Pathological Findings of Eimeria tenella in Desi Chickens with Morphometric Analysis of Oocysts - Veluchamy, Kumar; Thangathurai, R.; Ponnarasi, S.; Sugirtha, J.; Sakthidharana, P. (International Journal of Livestock Research, 2025)
Five numbers of three weeks old dead desi chickens were brought to the Department of Veterinary Pathology, Veterinary College and Research Institute, Tirunelveli for postmortem examination. External examination revealed emaciation with ruffled feathers and pale mucous membrane. On internal examination, liver showed multifocal pale areas, lung was congested and caecum lumen contained clotted blood with multifocal ecchymotic hemorrhages. Cytological examination of intestinal scrapings revealed the presence of numerous unsporulated oocysts appeared as oval to round shaped with double layered wall. Histopathological examination of internal organs showed, mild degeneration of hepatocytes and diphtheritic enteritis along with presence of numerous Eimeria tenella coccidial oocysts studded within the mucous membrane. The oocysts morphometric analysis was carried out in 40x magnification of light microscope. The values of Eimeria tenella oocysts like breadth, length and shape index were: 24.48µm, 30.84µm and 1.25µm, respectively. Based on cytological, histopathological and morphometry analysis of oocysts, the case was diagnosed as caecal coccidiosis caused by Eimeria tenella. The flock was treated with Amprolium hydrochloride 20% in drinking water for a period of 4 days and was advised to change the bedding material.